Effect of sperm DNA fragmentation on clinical outcomes for Chinese couples undergoing in vitro fertilization or intracytoplasmic sperm injection - Xue, Lin-Tao (J Int Med Res, 2016)
OBJECTIVE: To investigate the effect of sperm DNA fragmentation on the fertilization rate, embryo development and pregnancy outcome of in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) in a cohort of Chinese couples. METHODS: Infertile couples that had undergone assisted reproductive technology at our centre between January 2011 and December 2013 were included in this retrospective study. Fractions of prepared sperm samples were evaluated for sperm DNA fragmentation on the day of oocyte recovery. RESULTS: Of the 550 couples selected, 415 had undergone IVF and 135 ICSI. Sperm DNA fragmentation rate was significantly negatively correlated with the fertilization rate in the ICSI cycles but not the IVF cycles. No association was found between sperm DNA fragmentation and cleavage rate or good quality embryo formation rates in IVF or ICSI cycles. Receiver operating characteristic (ROC) curve analysis showed that the sperm DNA fragmentation rate was a statistically significant prognostic indicator of the clinical fertilization rate in ICSI cycles; a rate > 22.3% was associated with a lower fertilization rate following ICSI compared with a rate ≤ 22.3%. CONCLUSIONS: High values of sperm DNA fragmentation were associated with a low fertilization rate following ICSI but were not associated with alterations in pregnancy or live birth rates in either ICSI or IVF in this cohort of Chinese couples.